Sharia finance workshop for MSME in Bandar Lampung City - Aryan Danil Mirza. BR; Vitriyani Tri Purwaningsih; Dian Fajarini; Harsono Edwin Puspita (LPPM Universitas Lampung, 2022)
Running a business in a halal and blessed way is a necessity for Muslim entrepreneurs. To realize a good business, of course, good Islamic financial education is needed. The Service Team from FEB Unila took the initiative to provide training for MSMEs in Bandar Lampung City in the form of introducing sharia financial literacy so businesses can continue and comply with sharia values. We package this workshop activity in the Focus Group Discussion and Lecture methods, it allows participants to actively participate in this activity. We hoped that after participating in this activity, participants will open their horizons in recognizing the concept of Islamic finance, Islamic banking products and open access to capital from Islamic financial institutions.